1982
DOI: 10.1021/ja00378a027
|View full text |Cite
|
Sign up to set email alerts
|

A nitrogen-15 nuclear magnetic resonance study of the acid-base and tautomeric equilibriums of 4-substituted imidazoles and its relevance to the catalytic mechanism of .alpha.-lytic protease

Abstract: the electrode does not contain bulky substituents; (v) anthraquinones are adsorbed parallel to the surface and are not influenced by changes in concentration; (vi) the biphenyl moiety, initially adsorbed with both rings parallel to the surface, undergoes reorientation first to a structure in which both rings are bonded to the surface edgewise and then to a 1 2 structure in which one ring is attached and the other is pendant; (vii) preferential adsorption of organic functional groups on Pt follows the order thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 0 publications
3
48
0
Order By: Relevance
“…bExpected "N chemical shifts were derived from solution NMR studies of model compounds (Witanowski et al, 1972;Blomberg et al, 1977;Bachovchin & Roberts, 1978;Roberts et al, 1982;Bachovchin, 1986) and are consistent with solid-state NMR studies of imidazole and histidine (Harbison et al, 1981;Munowitz et al, 1982).…”
Section: Tautomeric States Of His-75 and His-90mentioning
confidence: 69%
See 3 more Smart Citations
“…bExpected "N chemical shifts were derived from solution NMR studies of model compounds (Witanowski et al, 1972;Blomberg et al, 1977;Bachovchin & Roberts, 1978;Roberts et al, 1982;Bachovchin, 1986) and are consistent with solid-state NMR studies of imidazole and histidine (Harbison et al, 1981;Munowitz et al, 1982).…”
Section: Tautomeric States Of His-75 and His-90mentioning
confidence: 69%
“…More recently, the presence of hydrogen bonds has been inferred from perturbations of "N chemical shifts from their canonical (non-hydrogenbonded) values. In a detailed study of "N chemical shifts of nitrogens in imidazole-based model compounds (Schuster & Roberts, 1979;Roberts et al, 1982), it was shown that type-a and type-a+ nitrogens acting as hydrogenbond donors show systematic downfield shifts (up to 10 ppm) relative to expected values (Table 2), whereas type-0 nitrogens acting as hydrogen-bond acceptors show systematic upfield shifts (up to 10 ppm). These data have been used to show that His-57 N"-H and His-57 NE2 of a-lytic protease are both involved in hydrogen bonds (Bachovchin, 1986).…”
Section: Active Site Of Iiigicmentioning
confidence: 99%
See 2 more Smart Citations
“…70 Hultquist's phosphoryl transfer experiments can be used as a plausible explanation for the accumulation of τ-pHis with the decrease in π-and bis-pHis over time (Scheme 3). Phosphoryl transfer reactions (1)(2)(3)(4)(5)(6)(7)(8) suggest that the phosphoryl group of pHis can be donated to the imidazole nitrogen of His or α-N-acetyl-His.…”
Section: Chemistry Of Phosphohistidinementioning
confidence: 99%